Highlighting the Dystonic Phenotype Related to GNAO1. Issue 7 (20th June 2022) - Wirth, Thomas; Garone, Giacomo; Kurian, Manju A.; Piton, Amélie; Millan, Francisca; Telegrafi, Aida; Drouot, Nathalie; Rudolf, Gabrielle; Chelly, Jamel; Marks, Warren; Burglen, Lydie; Demailly, Diane; et al.
Abstract: Background: Most reported patients carrying GNAO1 mutations showed a severe phenotype characterized by early‐onset epileptic encephalopathy and/or chorea. Objective: The aim was to characterize the clinical and genetic features of patients with mild GNAO1 ‐related phenotype with prominent movement disorders. Methods: We included patients diagnosed with GNAO1 ‐related movement disorders of delayed onset (>2 years). Patients experiencing either severe or profound intellectual disability or early‐onset epileptic encephalopathy were excluded. Results: Twenty‐four patients and 1 asymptomatic subject were included. All patients showed dystonia as prominent movement disorder. Dystonia was focal in 1, segmental in 6, multifocal in 4, and generalized in 13. Six patients showed adolescence or adulthood‐onset dystonia. Seven patients presented with parkinsonism and 3 with myoclonus. Dysarthria was observed in 19 patients. Mild and moderate ID were present in 10 and 2 patients, respectively. Conclusion: We highlighted a mild GNAO1 ‐related phenotype, including adolescent‐onset dystonia, broadening the clinical spectrum of this condition. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society